RENTABILITAS EKONOMI DITINJAU DARI ASPEK PERPUTARAN KAS DAN PERPUTARAN PIUTANG (STUDI KASUS PADA KOPERASI KREDIT TUKE LER HEWOKLOANG, MAUMERE) - Viktor Eko Transilvanus; rangga, yoseph darius purnama; Antonius Philipus Kurniawan Gheta; Cicilia Ayu Wulandari Nuwa (STEKOM PRESS, 2021)
ABSTRACT This study is aims to determine the effect of the level of (1) cash turnover against economic rentability, (2) the accounts receivable turnover against economic rentability, (3) cash turnover and accounts receivable turnover for economic rentability. Subjects in this study is a credit cooperative Tuke Ler Hewokloang and its object is cash turnover, accounts receivable turnover and economical rentability. The type of date in this study were collected quntitative data with documentation techniques and analyzed using multiple linier regression analysis. The Result of this study showed (1) the level of cash turnover does not affect the economic rentability, (2) the level of accounts receivable turnover ratehas an effect and not significant to economic rentability, (3) the level of cash turnover and accounts receivable turnover rates affect and significant the economic rentability in Credit Cooperative Tuke LerHewokloang. Keyword: cash turnover, receivable turnover, economic rentability.